Penerapan Metode Inkuiri dengan Teknik Copy the Master dalam Pembelajaran Menulis Cerpen di Kelas XII SMKN Terpadu Provinsi Riau - Fitri, Meliya; Liberti, Liberti; Vivinovarina, Vivinovarina; Yuliana, Yuliana (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This research investigates the effectiveness of the inquiry learning method employing the "copy the master" technique in enhancing short story writing skills among class XII students at the Agricultural Vocational School. The study employs action research methodology and involves class XII ATP-1, comprising 36 students. Findings reveal that the inquiry method, utilizing the "copy the master" technique, significantly improves short story writing abilities. Results from cycle I and II show an increase from an average score of 77.89 to 81.89, indicating a 4% improvement. The inquiry learning process involves steps such as reading the model writing, analyzing its content and form, creating a writing framework based on the model, and practicing writing by emulating the framework, ideas, or writing techniques from the model. This approach demonstrates promising potential for enhancing students' writing proficiency, offering valuable insights for educators seeking effective strategies to foster writing skills in vocational education settings.